TCR-CD3ζ gene polymorphisms and expression profile in rheumatoid arthritis. (2nd October 2016) - Li, Peng; Wang, Xiu; Zhao, Meng-Qin; Li, Lian-Ju; Zhang, Chao; Li, Bao-Zhu; Liu, Juan; Yang, Xiao-Ke; Leng, Rui-Xue; Fan, Yin-Guang; Pan, Hai-Feng; Ye, Dong-Qing
Abstract: Objectives : Recent evidence has demonstrated that CD3ζ (also called CD247) play a vital role in multiple autoimmune diseases. In this study, we explored the association between CD247 gene single-nucleotide polymorphisms (SNPs) and rheumatoid arthritis (RA) in a Chinese Han population. We also evaluated the CD3ζ expression profile in peripheral blood mononuclear cells (PBMCs) from patients with RA and health controls. Methods : Three CD247 polymorphisms ( rs704853, rs1214611 and rs858554 ) were studied in 612 patients with RA and 848 controls in a Chinese population. Genotyping was performed using the Fluidigm 192.24 Dynamic Array™ Integrated Fluidic Circuit (IFC). For gene expression study, CD3ζ mRNA levels of 36 patients with RA and 39 healthy individuals were assessed by real-time polymerase chain reaction (RT-PCR). Data were analyzed by SPSS 11.5 software. Results : A significant association between rs858554 polymorphism and RA was found under all genetic models (all p < 0.05). Moreover, we found the genotype distribution and allele frequency of rs858554 were significant associated with ACCP + and RF + phenotype as compare to health controls (all p < 0.05). Unfortunately, we did not detect any significant associations between rs704853, rs1214611 and RA susceptibility and autoantibody profiles (all p > 0.05). The gene expression assays showed that CD3ζ mRNA levels were downregulated in PBMCs of patients with RA when compared to healthy controls. Conclusions : Our results, the first reported for distinct Chinese populations, support a role of the CD247 gene in the susceptibility to RA. Further studies with more sample size are necessary to clarify the exact role of CD247 gene in the pathogenesis of RA.